“You have to get off the island to see the island”: Perspectives of Mentoring and Leadership in Schools Through the Internationalization of Teacher Education in Brazilian Basic Education - Gildete Cecilia Neri Santos Teles; Annette Cregan (Vértices)
This study explores the role of responsible internationalization in Brazilian Basic Education, focusing on mentoring and collaborative leadership in schools. The objective is to analyze how the exchange of good practices between different educational realities, such as the Irish and Brazilian, can strengthen the development of teacher leadership. The methodology is based on qualitative research, centered on the authors’ experiences during the professional development program held in Ireland between 2023 and 2024 by CAPES. Preliminary results highlight the importance of collaborative professionalism in addressing common school challenges, including resistance to change and limited resources. It concludes that responsible internationalization can enhance educational transformation.